Bicornis unicollis uterus as a risk factor of preterm birth: A case of young woman with multiple premature births - Hasanuddin, Hasanuddin; Maharani, Cut R.; Nora, Hilwah; Roziana, Roziana; Aditya, Rizka; Dewi, Tgk. Puspa; Qadri, Sofyan (Narra J, 2023)
Bicornis unicollis uterus is a rare congenital uterine abnormality that occurs due to the failure of Mullerian duct fusion early in the development of the female internal genitalia system. In this case report, we present a woman with bicornis unicollis uterus who had preterm birth. A 30-year-old female patient with two caesarean sections history with premature babies was presented to the hospital with a complaint of regular contractions for twelve hours in her third preterm pregnancy. The patient has no particular symptoms besides acute abdominal pain. The ultrasonography examination indicated a uterus didelphys with breech presentation fetus. Due to the patient’s caesarean history and the fetal presentation, an emergency caesarean section was decided and performed. It was found that the gravid uterus was on the left and the baby was subsequently delivered with a complete placenta. Postoperative condition of the patient was shown to be stable while the baby underwent an intensive care at the neonatal intensive care unit. This case report highlights that early diagnosis in this rare case is critical since bicornis unicollis uterus are mostly asymptomatic. Caesarean section was chosen in the present case based on consideration of the fetal and maternal clinical conditions.